(4.8x+8x)=(6.8-6.8)

Simple and best practice solution for (4.8x+8x)=(6.8-6.8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4.8x+8x)=(6.8-6.8) equation:


Simplifying
(4.8x + 8x) = (6.8 + -6.8)

Combine like terms: 4.8x + 8x = 12.8x
(12.8x) = (6.8 + -6.8)
(12.8x) = (6.8 + -6.8)

Combine like terms: 6.8 + -6.8 = 0.0
(12.8x) = (0.0)
(12.8x) = 0.0

Solving
(12.8x) = 0.0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '12.8'.
x = 0

Simplifying
x = 0

See similar equations:

| 3t+6=-4 | | (5z-6y)(5z+6y)= | | (4.8x+8x)(6.8-6.8)= | | 3[x+2]=9 | | (5z-6y)(5z+6)= | | 3x(n+.333)=2 | | (4.8x+8x)= | | x^2+88x=0 | | 5-3(2x-1)=4(x-5)+6 | | (19p^8q^2)x(-5p^7q^7)= | | 230=-75x+5 | | 14=5z | | 6+8=5z | | 3(4x+1)=2x-8x | | 3x-(3-4)=-17 | | 12cosx-6=0 | | 3(4x-1)=2x-8x | | 2x^4+7x^3-3x^2-5x-1=0 | | (-11)/(16x) | | 15-2c=7 | | 5/9(F-32)=-62.1 | | t=3n+3 | | 2(x+1)=3x+-3 | | 81-7+6= | | -6=n/3-10 | | 32x+24y+64= | | 9*x^6+15*x^4-x^2-6*x+1=0 | | 5/9(F-32)=25 | | 2n-14=81 | | 7(v+4)-3v=2(2v+2)-11 | | k5.2+81.9=47.2 | | v^2-3vf-70f^2=0 |

Equations solver categories